Affine Disagreement and Asset Pricing - Chen, Hui; Joslin, Scott; Tran, Ngoc-Khanh (American Economic Review, 2010)
Models of heterogeneous beliefs can generate rich implications for trading and asset pricing (see Suleyman Basak 2005 for a recent survey). When studying such models, aggregation often leads to difficulty in computing equilibrium outcomes. In this paper, we introduce a flexible framework to model heterogeneous beliefs in the economy, which we refer to as “affine’’ disagreement about fundamentals. Affine processes (see Darrel Duffie, Jun Pan, and Kenneth Singleton 2000) are appealing as they provide a large degree of flexibility in modeling the conditional means, volatilities, and jumps for various quantities of interest while remaining analytically tractable. Our affine heterogeneous beliefs framework allows further for stochastic disagreement among agents about growth rates, volatility dynamics, as well as the likelihood of jumps and the distribution of jump sizes.